Cost Of Acquiring And Operating Mineral Properties - Part 1. Metal, Nonmetallic, And Coal - Paul M. Tyler (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1964)
Mineral raw materials, because they are essential to our industrial prosperity and military strength, must be made available in substantial quantities regardless of cost. Variations in the cost of procuring minerals, as compared with the cost of obtaining other commodities, and changes in the cost of production of different minerals relative to one another, will naturally influence the quantities of a given mineral item that can be marketed readily. However, in the last analysis, the cost of winning minerals from the ground usually constitutes only a small fraction of the value of the end-use products and services derived from them. The miner's share of the cost of a typewriter, telephone circuit, or even a modem office building, is almost insignificant. Far more important to the ultimate consumer, therefore, than any minor saving in cost is the assurance of ample supplies of the minerals needed to aliment our expanding economy. To create a successful metal mining operation involves (1 ) the discovery and systematic development of a mineral deposit, (2) extraction of the ore, (3) the mechanical and metallurgical processing to eliminate worthless or harmful impurities, and (4) the profitable disposal of the product. The fist step of the technological process belongs chiefly in the realm of the geologist, the second is a mining engineer's job, the third is mainly up to the millmen and extractive metallurgists; whereas the fourth and equally important step poses a commercial problem that has aspects in common with the marketing of other products. Ore finding is far from being an exact science. There is no mathematical criterion for evaluating the efficiency of prospecting and exploration. Lady Luck shares the honors or assumes part of the blame along with the prospector and geologist. Marketing like- wise involves factors that seemingly defy engineering analysis. Although the other steps can be measured with some degree of mathematical accuracy, even they tend to vary so widely in basic principle, as well as in